Mall & Market Design; a Neo-Vernacular Approach (International Journal of Architecture and Urbanism, 2020)
The traditional market is a trade sector with its characteristics, such as the interaction between sellers and buyers when bargaining for merchandise. Nowadays, its presence, especially in Medan, is getting replaced by the presence of modern markets such as shopping centers because the market conditions themselves are increasingly shabby and unkempt over time. Thus, people will become more shifting to the shopping center, which is cleaner, safer, and have more varied sales. Therefore, lots of efforts have been made by the government by issuing policies such as the presence of the Build Operate Transfer (BOT) system, the rebuilding of traditional markets, and the rearrangement and redevelopment of traditional markets to compete with modern markets. With the Neo-Vernacular Architecture approach, the project will design by lifting local wisdom around the design area. Medan Tembung, Aksara, as the selected site, is quite strategic, which is the site of ex-Buana Plaza that has burned along its market, also located on one of the main routes to the highway gate of Kualanamu, and is an area with cultural values ​​that still exist but began to disappear. Through this design, it’s expected to increase the return of public interest to traditional markets and also improve the regional economy that also does not forget to raise local wisdom.